Zur Epidemiologie von Dientamoeba fragilis Jepps et Dobell, 1918. 4. Nachweis von Dientamoeba fragilis in enterobius Eiern mit Hilfe von IEP-bestimmungen - Ockert, G; Schmidt, T (Journal of hygiene, epidemiology, microbiology, and immunology, 1976)
By means of the method of determining the isoelectric point, the same conditions of absorption and stain intensity as in Dientamoeba cultivation forms were determined in cells found in Enterobius vermicularis eggs of Dientamoeba fragilis carried. By that way, identity of both stages, as well as function of pinworms as Dientamoeba fragilis vectors were confirmed.
Keywords: Isoelectric Point; ovum; Ovum; Disease Vectors; ženské pohlaví; zvířata; Enterobius; Female; Dientamoeba; infekce přenášené vektorem; izoelektrický bod; Animals